Evaluation of sleep structure in children of 2 to 12 years of age with obstructive sleep apnea proven by polysomnography: Sleep structure of children with OSA - Jalilalghadr, Shabnam; Taher-Ahmadi, Hasan; Nozari, Hoormehr; Taghiloo, Manouchehr (Chronic Diseases Journal, 2024)
BACKGROUND: Identifying children with sleep-disordered breathing (SDB) and treating them early is essential. This study was conducted to determine the structure of sleep in children with obstructive sleep apnea (OSA). METHODS: This cross-sectional, retrospective-descriptive study was performed in the sleep center of Qods Hospital, Qazvin City, Iran, from April 2017 to June 2021. Using simple random sampling, 46 children and adolescents aged 2-12 years, who underwent polysomnography, were selected. Electroencephalography (EEG), chin and limbs electrooculography (EOG) and electromyography (EMG), and electrocardiogram (ECG) electrodes were implanted. The information recorded using polysomnography were interpreted manually according to the standards of the American Academy of Sleep Medicine (AASM). Due to the quality of the data, frequency distribution tables were used to analyze the data. RESULTS: Among the 33 patients with OSA included in the study, 24 (72.72%) patients had severe OSA and 9 (27.3%) patients had moderate OSA. The mean of respiratory disorders in each patient included: 6.73% central apnea, 58.92% obstructive apnea, 3.87% mixed apnea, and 30.45% hypopnea. The average total sleep time (TST) was 6 hours and 47 minutes. Furthermore, the mean hypopnea apnea index (AHI) was 30.86 per hour. Sleep structure consisted of 9.03% stage N1, 51.33% stage N2, 23.18% stage N3, and 14.39% rapid eye movement sleep (REM). Sleep efficiency was estimated to be 79.57% CONCLUSION: Sleep apnea-disordered breathing including severe OSA, moderate apnea, central apnea, obstructive apnea, and mixed apnea-hypopnea were observed in the studied children.